The literature review six steps to success - Machi, Lawrence A.; McEvoy, Brenda T. (Corwin, a SAGE Company, 2016)
Graduate students who turn in exceptional literature reviews are recognized as excellent critical thinkers as well as masters of academic argumentation, research writing, and academic writing. This six-step process pioneered by this book has made the task fluid and seamless.